Interpretation of Image Symbols in Tourist Destinations based on Network Text Analysis: A Case Study of Lu’an - Kong, Li; Zhao, Huayi (International Journal of Social Sciences and Public Administration, 2024)
A good image of a tourist destination is the core competitiveness and a strong factor to attract tourists. The large use of new media in life and the popularization of the Internet make the online text gradually become an important means for tourists to obtain the tourist destination information. Taking Lu ’an as an example, based on the online travel notes collected by Ctrip, Qunar and Hornet’ s Nest tourism websites, this paper uses ROST Content Mining6 to perceive the tourist destination, and found that tourists have a strong perception of natural tourism resources and low experience of transportation, accommodation and other tourism reception facilities. Lu ’an should develop targeted tourism products with local characteristics, improve tourism service facilities, design diversified tourism routes to improve tourists’ satisfaction and improve the image of a tourist destination.